Cues to Opening Mechanisms From in Silico Electric Field Excitation of Cx26 Hemichannel and in Vitro Mutagenesis Studies in HeLa Transfectans - Zonta, Francesco; Buratto, Damiano; Crispino, Giulia; Carrer, Andrea; Bruno, Francesca; Yang, Guang; Mammano, Fabio; Pantano, Sergio (Frontiers in Molecular Neuroscience, 2018)
Connexin channels play numerous essential roles in virtually every organ by mediating solute exchange between adjacent cells, or between cytoplasm and extracellular milieu. Our understanding of the structure-function relationship of connexin channels relies on X-ray crystallographic data for human connexin 26 (hCx26) intercellular gap junction channels. Comparison of experimental data and molecular dynamics simulations suggests that the published structures represent neither fully-open nor closed configurations. To facilitate the search for alternative stable configurations, we developed a coarse grained (CG) molecular model of the hCx26 hemichannel and studied its responses to external electric fields. When challenged by a field of 0.06 V/nm, the hemichannel relaxed towards a novel configuration characterized by a widened pore and an increased bending of the second transmembrane helix (TM2) at the level of the conserved Pro87. A point mutation that inhibited such transition in our simulations impeded hemichannel opening in electrophysiology and dye uptake experiments conducted on HeLa tranfectants. These results suggest that the hCx26 hemichannel uses a global degree of freedom to transit between different configuration states, which may be shared among the whole connexin family.